Supplementation with active vitamin D3 ameliorates experimental autoimmune thyroiditis in mice by modulating the differentiation and functionality of intrathyroidal T-cell subsets - Wang, Chun-Mei; Chen, Ying-Jie; Yang, Bo-Cheng; Yang, Jia-Wen; Wang, Wei; Zeng, Yang; Jiang, Jun (Frontiers in Immunology, 2025)
ObjectivePeople with Hashimoto’s thyroiditis (HT) often have low vitamin D3 concentrations. Some research has suggested that vitamin D3 supplementation reduces thyroid inflammation, but this remains controversial.MethodsEAT was induced in female NOD/ShiLtJ mice by giving them water containing 0.05% sodium iodide, and 1μg/kg of 1α,25-(OH)2D3 was injected intraperitoneally every other day. After 8 weeks, the morphological architecture of the mouse thyroid follicles was examined by histological sections, thyroid autoantibodies and thyroid hormone concentrations were determined by enzyme-linked immunosorbent assays (ELISAs), and the major functions and subsets of B- and T-lymphocytes in the mouse thyroid were determined by tissue multiple immunofluorescence technology and ELISA.ResultsEAT caused thyroiditis follicle destruction and interfollicular lymphocyte infiltration in mice, increased concentrations of circulating thyroid autoimmune antibodies TG-Ab and TPO-Ab, and abnormal thyroid hormone levels. EAT also increased the number and functionality of CD4+ Tfh, Th17,Th1 and Th2 cells in the thyroid, while decreasing the number and functionality of CD4+ Treg cells and CD19+B10 cells. Treatment with VD3 reversed these changes.ConclusionVitamin D3 supplementation can effectively treat autoimmune thyroiditis in mice. VD3 reduces autoimmune thyroid damage and decreases serum thyroid antibody levels in mice by inhibiting the differentiation and functionality of pro-inflammatory Tfh, Th17, Th1 and Th2 cells and by facilitating the differentiation and functionality of anti-inflammatory B10 cells and Treg.